Instant Messaging: Effects of Relevance and Timing - Czerwinski, Mary; Cutrell, Ed; Horvitz, Eric (People and Computers XIV: Proceedings of HCI 2000, 2000)
Instant messaging (IM) has grown rapidly to involve millions of users spanning a variety of platforms. This paper outlines two preliminary studies that examined the effects of IM notifications on ongoing desktop computer productivity tasks. Results from the studies show that the disruptiveness of IM to productivity tasks is reduced if the incoming message is highly relevant to the current task, or if messages are queued until certain key computing operations have been completed. User interface design principles for the control of messaging are proposed based on the results.